Pengaruh Promosi, Kualitas Pelayanan, dan Kualitas Produk terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan sebagai Variabel Mediasi pada Outlet Haus! di Depok - Zuhad Ichyaudin; Riki Ferdinan Hutapea (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2025)
The purpose of this research is to determine and analyze the influence of Promotion, Service Quality, and Product Quality on Customer Loyalty for beverages at the Haus! outlet in Depok, with Customer Satisfaction as an intervening variable. The sample for this research consists of customers who have purchased Haus! beverages in Depok and reside in Depok. The sampling technique used the Lemeshow formula. The research sample consisted of 150 respondents, and the data collection method employed a questionnaire instrument. The method used is Partial Least Square with the help of SmartPLS 3.0 software, including Convergent Validity Test, Discriminant Validity, Average Variance Extracted (AVE), Composite Reliability Test, R-Square Test, Hypothesis Test, Path Coefficient, and Specific Indirect Effect. The Path Coefficient test results show that Promotion, Service Quality, and Product Quality have an impact on Customer Satisfaction. Service Quality and Product Quality affect Customer Loyalty. However, Promotion does not affect Customer Loyalty. The results of the Specific Indirect Effect test show that Promotion, Service Quality, and Product Quality affect Customer Loyalty through Customer Satisfaction.